2013
DOI: 10.1016/j.molcel.2013.09.016
|View full text |Cite
|
Sign up to set email alerts
|

The Folliculin Tumor Suppressor Is a GAP for the RagC/D GTPases That Signal Amino Acid Levels to mTORC1

Abstract: SUMMARY The mTORC1 kinase is a master growth regulator that senses numerous environmental cues, including amino acids. The Rag GTPases interact with mTORC1 and signal amino acid sufficiency by promoting the translocation of mTORC1 to the lysosomal surface, its site of activation. The Rags are unusual GTPases in that they function as obligate heterodimers, which consist of RagA or B bound to RagC or D. While the loading of RagA/B with GTP initiates amino acid signaling to mTORC1, the role of RagC/D is unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
550
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(583 citation statements)
references
References 72 publications
26
550
2
1
Order By: Relevance
“…Several additional mechanisms through which amino acids regulate mTORC1 signaling have also recently been reported, including the identification of the Folliculin-FNIP2 complex as a GAP for RagC/D that activates mTORC1 in the presence of amino acids (Petit et al, 2013;Tsun et al, 2013). Another study found that the amino acid glutamine, which is utilized as a nitrogen and energy source by proliferating cells, activates mTORC1 independently of the Rag GTPases through the related Arf family GTPases (Jewell et al, 2015).…”
Section: Upstream Of Mtorc1mentioning
confidence: 93%
“…Several additional mechanisms through which amino acids regulate mTORC1 signaling have also recently been reported, including the identification of the Folliculin-FNIP2 complex as a GAP for RagC/D that activates mTORC1 in the presence of amino acids (Petit et al, 2013;Tsun et al, 2013). Another study found that the amino acid glutamine, which is utilized as a nitrogen and energy source by proliferating cells, activates mTORC1 independently of the Rag GTPases through the related Arf family GTPases (Jewell et al, 2015).…”
Section: Upstream Of Mtorc1mentioning
confidence: 93%
“…22 No changes in the colocalization between FLCN and lysosomes were observed upon Baf exposure ( Fig. 7A and B).…”
Section: Baf Activated Mtorc1 Independent Of Nutritionmentioning
confidence: 91%
“…19 The nucleotide bound state of RRAGC/D is regulated by FLCN (folliculin), which also functions as a GAP. 20 We reported previously that TFEB is regulated by MTORC1, 8 but TFEB regulation by MTORC1 is complex and cell context-dependent. 8,21 Nutrient deprivation leads to MTORC1 inhibition, reduces TFEB phosphorylation, and promotes TFEB nuclear translocation and expression of lysosomal genes.…”
Section: Introductionmentioning
confidence: 92%